A Microfluidic Paper-Based Device for Monitoring Urease Activity in Saliva - Francisca T. S. M. Ferreira; António O. S. S. Rangel; Raquel B. R. Mesquita (Biosensors)
Chronic Kidney Disease (CKD) is a disorder that affects over 10% of the global population, and that would benefit from innovative methodologies that would provide early detection. Since it has been reported that there are high levels of urease in CKD patients’ saliva, this sample is a promising non-invasive alternative to blood for CKD detection and monitoring. This work introduces a novel 3D µPAD for quantifying urease activity in saliva in a range of 0.041–0.750 U/mL, with limits of detection and quantification of 0.012 and 0.041 U/mL, respectively. The device uses the urease in the sample to convert urea into ammonia, causing a colorimetric change in the bromothymol blue. The accuracy of the developed device was evaluated by comparing the measurements of several saliva samples (#13) obtained with the μPAD and with a commercially available kit. Stability studies were also performed to assess its functionality as a point-of-care methodology, and the device was stable for 4 months when stored in a vacuum. After the sample placement, it could be scanned within 40 min without providing significantly different results. The developed device quantifies urease activity in saliva within 30 min, providing a simple, portable, lab-free alternative to existing methodologies.